ANALISIS KANDUNGAN C-ORGANIK DAN TOTAL MIKROB PADA BEBERAPA JENIS TANAH - Jufri, Afifah Farida; Rahmi, Eka; Agustini, Rika Yayu; Rosalina, Febrianti (Agros Journal of Agriculture Science, 2024)
The level of soil fertility is a crucial factor in the success of agricultural businesses because it is the main medium for growing crops. Soil fertility will continue to decrease if it is managed continuously without understanding the condition of the soil, so it is necessary to evaluate the condition of the soil before carrying out plant cultivation activities. One indicator of soil fertility is the organic matter content (C-Organic) and the total availability of soil microbes. This research aims to evaluate the organic matter (C-Organic) content and total microbes from different soil types and conditions. This research took place for 2 months at the Land Physical Resources Development Laboratory and the Soil Chemistry and Fertility Laboratory, Department of Soil Science and Land Resources, Faculty of Agriculture, Bogor Agricultural Institute. The soil samples used were taken from several locations, namely the Cikabayan IPB oil palm experimental plantation, IPB experimental rice fields, IPB rubber plantations and peat soil from Jambi. The research results show that the highest organic matter content was found in Jambi peat soil, but the highest total microbes and microbial activity were found in oil palm soil. The topsoil layer contains more C-Organic than sub-soil, and paddy soil contains the lowest C-Organic, total microbial and soil respiration. . Organic C content and total microbes are not the only ones that determine the level of respiration in soil, there are other factors such as temperature.Key-words: microbes, soil fertility, soil evaluation INTISARI Tingkat kesuburan tanah merupakan faktor krusial dalam keberhasilan usaha pertanian karena merupakan media utama dalam budidaya tanaman. Kesuburan tanah akan terus berkurang jika dikelola terus menerus tanpa memahami kondisi tanah, sehingga perlu melakukan evaluasi kondisi tanah sebelum melakukan kegiatan budidaya tanaman. Salah satu indikator kesuburan tanah adalah kandungan bahan organik (C-Organik) dan ketersediaan total mikrob tanah. Tujuan penelitian ini untuk mengevaluasi kandungan bahan organik (C-Organik) dan total mikroba dari jenis dan kondisi tanah yang berbeda. Penelitian berlangsung selama 2 bulan di Laboratorium Pengembangan Sumberdaya Fisik Lahan dan Laboratorium Kimia dan Kesuburan Tanah, Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, Institut Pertanian Bogor. Sampel tanah yang digunakan diambil dari beberapa lokasi yang diambil dari kebun percobaan kelapa sawit Cikabayan IPB, tanah sawah percobaaan IPB, kebun karet IPB dan tanah gambut dari Jambi. Hasil penelitian menunjukkan bahwa kandungan bahan organik tertinggi terdapat pada tanah Gambut Jambi, namun total mikroba dan aktivitas mikroba tertinggi terdapat pada tanah kelapa sawit. lapisan tanah top soil mengandung lebih banyak C-Organik daripada sub soil, dan tanah sawah mengandung C-Organik, total mikroba dan respirasi tanah yang paling rendah. . Kandungan C-Organik dan total mikroba bukan satu-satunya yang menentukan tinggi rendahnya respirasi pada tanah, tetapi ada faktor lain seperti suhu.  Kata kunci: evaluasi tanah, kesuburan tanah, mikroba